Effectiveness of Multi-Frames Video Recorded Experiments on Pre-University Students’ Achievement for Capacitor Topic - Ramly, Rosazley; Jaafar, Rosly; Mat Daud, Anis Nazihah; Ali, Shaharudin; Wan Mokhtar, Wan Zul Adli; Haron, Roszairi; Moahmed Safian, Nur Azmina (EDUCATUM Journal of Science, Mathematics and Technology, 2016)
The aim of this study is to determine the effectiveness of multi-frames video recorded experiments (MFVREs) on pre-university students’ achievement for capacitor topic. This study was carried out among 60 Diploma Science students of Universiti Pendidikan Sultan Idris, Malaysia. Students’ pre-test and post-test scores were analyzed using independent sample t-test. The effectiveness of MFVREs on students’ achievement were analyzed for four subtopics of capacitor: basic concept of capacitor (S1), series connection of capacitors (S2), parallel connection of capacitors (S3) and combination of series and parallel connection of capacitors (S4). Findings revealed that MFVREs give significant effects on students’ achievement for S2, S3 and S4 subtopics but no significant effect to students’ achievement for S1 subtopic compared to PowerPoint slides. Thus, MFVREs approach can be used either as a teaching aid in normal classroom or a student-centered learning video in order to improve the achievement of pre-university students for physics subject.